Molecular beam epitaxy, photocatalytic solar water splitting, and carrier dynamics of InGaN micro-network deep-nano structures - Ishtiaque Ahmed Navid; Yifan Shen; Peng Zhou; Jonathan Schwartz; Yin Min Goh; Tao Ma; Robert Hovden; Theodore Norris; Zetian Mi (AIP Advances)
GaN-based nanostructures are increasingly being used for a broad range of electronic as well as optoelectronic device applications, and more recently artificial photosynthesis and solar fuel generation. We have performed a detailed investigation of the molecular beam epitaxy and characterization of Mg-doped p-type InGaN micro-network nanostructures with lateral dimensions reaching as small as a few nanometers. Mg doping shows a clear impact on the carrier dynamics and photocatalytic performance of such micro-network nanostructures. The p-type InGaN micro-network nanostructures exhibit remarkable photocatalytic activities for solar water splitting and hydrogen fuel generation. With an optimum level of Mg doping, we demonstrate a solar-to-hydrogen (STH) conversion efficiency of ∼2.6% in the photocatalytic water splitting process under concentrated sunlight at ∼50 °C temperature. The impact of Mg doping variation on the STH conversion efficiency and carrier dynamics has been investigated in detail. This study provides new directions for developing the next generation of high-efficiency photocatalytic nanostructure devices and systems.